Building a Herbal Medicine Ontology Aligned with Symptoms and Diseases Ontologies – - Bassel Alkhatib; Dania Briman (Journal of Digital Information Management, 2018)
The use of traditional medicine is increasing rapidly in many societies due to its efficiency and affordability. The locally available herbs are basically used in the treatment of symptoms and diseases. Herbal Medicines have proved effective in many cases and outperformed the chemical drugs.